23.0k views
1 vote
Please Help!!!!!!!

Simplify
g(5c+4)= (5c+4)^2+8(5c+4)-24

Please show all your work!!

User Szpic
by
6.1k points

2 Answers

1 vote

Answer: (5c+4)^2+40c+8 over 5c+4

Explanation:

User ChuckO
by
5.8k points
3 votes

Answer:

STEP n1:

Equation at the end of step 1

(g•(5c+4))-((((5c+4)2)+8•(5c+4))-2) = 0

STEP 2:

Equation at the end of step 2

g • (5c + 4) - (25c2 + 80c + 46) = 0

STEP 3:

Equation at the end of step 3

5gc + 4g - 25c2 - 80c - 46 = 0

STEP 4:

Solving a Single Variable Equation

4.1 Solve 5gc+4g-25c2-80c-46 = 0

User Turtlepower
by
6.1k points